Preparation and ferroelectric properties of pyrochlore-free Pb(Ni 1/3Nb2/3)O3-based solid solutions - Vittayakorn, N.; Cann, D. P. (My University, 2007)
Polycrystalline ceramics of the perovskite solid solution 0.5Pb(Ni 1/3Nb2/3)O3-(0.5-x)-Pb(Zn1/3Nb 2/3)O3-xPb(Zr1/2Ti1/2)O 3; x=0.0-0.5 (PNN-PZN-PZT) were synthesized by a modified columbite method. Highly dense ceramics lacking parasitic pyrochlore phases were prepared at a calcination temperature of 950 °C by using a double-crucible configuration, excess PbO (2 mol∈%), and a fast heating/cooling rate (20 °C/min). The ceramics were characterized by a variety of techniques including X-ray diffraction, ferroelectric hysteresis loop measurements, field-induced longitudinal strain measurements, and electron microscopy. It was observed that the remanent polarization exhibited a significant increase with increasing x. In addition, the squareness of the hysteresis loop increased quasi-linearly as the molar fraction of PZT increased. The maximum spontaneous polarization and remanent polarization for the x=0.5 composition were 31.9 μC/cm2 and 25.2 μC/cm2, respectively. Moreover, the data were analyzed to show the evolution of the micro-domain state as a function of the molar fraction of PZT. © Springer-Verlag 2007.